Reguladores vegetais e alguns nutrientes minerais no desenvolvimento de plantas de tomateiro Pizzadoro enxertadas e não enxertadas - Silva, Janaína Oliveira da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The tomato (Solanum lycopersicum L.) is a dicotyledonous belongs to the Solanaceae family and due to their range of cultivation, this vegetable is already considered cosmopolitan, being the world's second largest crop after the potato. The productivity of any culture, especially the tomato, is directly linked to the way of farming, use of products and environmental variation. Among these, the use of synthetic chemicals has increased over the years and currently can be considered essential for the proper development of culture. An example of this practice is the use of synthetic biochemical compounds, such as plant growth regulators, which enhance the growth and development of culture. Thus, the present study was to evaluate the effect of plant growth regulators and nutrients in hybrid tomato plants 'Pizzadoro' ungrafted and grafted onto rootstock Guardian in plant development and crop productivity. The experimental design was factorial 7x2, with seven treatments and two types of plants. The activities of antioxidant enzymes (superoxide dismutase, peroxidase, catalase) were evaluated; lipid peroxidation; physical characterization and fruit of chemistry; and final yield. For the enzymatic evaluation were made three collections: at 60, 74 and 88 days after transplanting (DAT). For the quality of the fruit was selected referring to the fourth harvest fruit bunch. There was interaction between treatments and between the type of plant for enzyme activity and lipid peroxidation, showing that there was little oxidative stress in grafted plants compared to non-grafted. For pH, titratable acidity, soluble solids and ascorbic acid did not differ between treatments and also to the type of plant. The final yield for both total and marketable fruit fruits was higher in grafted plants

O tomateiro (Solanum lycopersicum L.) é uma dicotiledônea pertencente à família Solanaceae e devido a sua amplitude de cultivo, essa hortaliça já é considerada cosmopolita, sendo a segunda maior cultura mundial, depois da batata. A produtividade de qualquer cultura, principalmente a do tomate, está diretamente ligada à forma de cultivo, utilização de produtos e a variação ambiental. Dentre estas, a utilização de produtos químicos sintéticos tem aumentado ao longo dos anos e, atualmente, pode ser considerada essencial para o bom desenvolvimento da cultura.Exemplo dessa pratica é a utilização de compostos bioquímicos sintéticos, como os reguladores vegetais, que incrementam o crescimento e desenvolvimento da cultura. Dessa forma, o presente trabalho teve o objetivo de avaliar o efeito da aplicação de reguladores vegetais e nutrientes em plantas de tomate híbrido 'Pizzadoro' pé franco e enxertada em portaenxerto Guardião no desenvolvimento das plantas e na produtividade da cultura. O delineamento experimental foi fatorial de 7x2, sendo sete tratamentos e dois tipos de plantas. Foram avaliadas as atividades de enzimas antioxidantes (superóxido dismutase, peroxidase, catalase); a peroxidação de lipídios; caracterização física e química do fruto; e produtividade final.Para a avaliação enzimática foram feitas três coletas: aos 60, 74 e 88 dias após o transplante (DAT). Para a qualidade do fruto, foi selecionado a colheita referente ao quarto cacho de frutos. Observou-se interaçãoentre os tratamentos e entre o tipo de planta para atividade enzimática e peroxidação de lipídios, mostrando que houve pouco estresse oxidativo nas plantas enxertadas comparadas com as nãoenxertadas.Para pH, acidez titulável, sólidos solúveis totais e ácido ascórbiconão houve diferença entre os tratamentos e também com o tipo de planta. A produtividade final, ...
Growth regulators in the development of tomato (solanum lycopersicum l.) hybrid pizzadoro grafted and non-grafted
Keywords: Tomate - Pós-colheita; Produtividade agrícola; Enzimas; Hormonios vegetais; Tomato products